2004
DOI: 10.1111/j.0013-9580.2004.56903.x
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related Quality of Life of People with Epilepsy Compared with a General Reference Population: A Tunisian Study

Abstract: Summary:Purpose: The goal of the study was to assess the health-related quality of life (HRQOL) of persons with epilepsy (PWE) by using the short form survey 36 , to compare it with that of a control group and to detect factors influencing it.Methods: We collected clinical and demographic data and information on health status by using the Arabic translation of the SF-36 questionnaire from two groups: (a) 120 PWE consulting our outpatient clinic during a period of 4 months, and (b) 110 Tunisian citizens, repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
53
5
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 22 publications
19
53
5
2
Order By: Relevance
“…Guekht et al, reported that patients with frequent seizures had low social contact and feelings of stigmatisation. 32 Considerable emphasis has been placed on the 14,18,25 In the present study, no significant association was found between the number of drugs and QOL. However, epileptic patients who were taking one antiepileptic drug had a slightly higher QOL score than those on multiple drugs.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Guekht et al, reported that patients with frequent seizures had low social contact and feelings of stigmatisation. 32 Considerable emphasis has been placed on the 14,18,25 In the present study, no significant association was found between the number of drugs and QOL. However, epileptic patients who were taking one antiepileptic drug had a slightly higher QOL score than those on multiple drugs.…”
Section: Discussioncontrasting
confidence: 57%
“…Such a result is consistent with many previous studies that have been done in Iran, the Arabian Gulf, the Near East, Thailand, Norway, the UK, Russia, and Tunisia. 14,18,[29][30][31][32] The epileptic patients' rather poor QOL may be explained by the disease's chronicity (the mean duration of patients' illness in this study was 10.6 years), a result which was reported by Sillanpää et al, or because most of the epileptic patients in this study (78.4%) had not been seizurefree in the last year. Seizure frequency was described as one of the most relevant determinants of poor QOL.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Unsurprisingly, our finding similarly mirrored that of a Georgian study in 115 adult epilepsy out-patients-they had also managed to identify advanced age as a significant predictor coupled with strong correlation to low Overall QoL (Djibuti and Shakarishvili 2003). In South Korea and Tunisia, the significance of old age in relation to low HRQoL was uncovered (Choi-Kwon et al 2003;Mrabet et al 2004).…”
Section: Discussionsupporting
confidence: 81%